Mera tiraṅgā jīwana : Aṅgrezī pusataka I led three lives dā Pañjābī anuwāda - Philbrick, Herbert A. (Herbert Arthur), 1915-1993 (SAMP early 20th-century Indian books project, 1952)
Autobiography of communist and counterspy from America.